Layer-by-layer structured nanocomposite deposits from plasma-synthesized organosilicon nanoparticles and organosilicon nanoparticles decorated with Ag nanoparticles by taking advantage of cyclic nanoparticle formation in Ar/HMDSO reactive plasmas - Bérard, Rémi; Garofano, Vincent; Joblin, Christine; Stafford, Luc; Makasheva, Kremena (Frontiers in Nanotechnology, 2024)
Rational engineering of thin nanocomposite layers, deposited in reactive plasmas, requires knowledge on the plasma behavior in order to produce multifunctional deposits with tailored properties (structural, optical, electrical, etc.) This work presents an experimental study of nanoparticles synthesized in the plasma gas-phase and their subsequent use as building-blocks to form layer-by-layer nanostructures. The experiment is performed in a plasma process that successfully combines plasma polymerization of an organosilicon molecular precursor (hexamethyldisiloxane, HMDSO) and sputtering of a metallic (silver) target. Pulsed injection of the precursor is found to promote cyclic nanoparticle formation in Ar/HMDSO reactive plasmas. The plasma electron temperature is found to vary in the range 1.6 – 2.2 eV as derived from time-resolved optical emission spectroscopy of the plasma energetic conditions. This diagnostic method is also shown to provide a reliable tool for online monitoring of the nanoparticle synthesis process. Two types of layer-by-layer structured nanocomposites can be obtained depending on the type of nanoparticles synthesized: (i) organosilicon nanoparticles of size less than 100 nm in all studied plasma conditions for a large quantity of injected HMDSO and (ii) raspberry-like nanoparticles of size less than 150 nm when the quantity of injected HMDSO is reduced. The organosilicon nanoparticles growth follows a polydimethylsiloxane (PDMS)-like oligomerization scheme in which the R2-Si(-O)2 silicon bond tends towards the formation of polymeric structure in a R3-Si(-O)1 silicon chemical environment, containing Si-(CH2)-Si type bridges that are involved in cross-linking. The elemental composition of the raspberry-like nanoparticles is similar to that of the organosilicon nanoparticles, supplemented by the Ag component. The decorating silver nanoparticles are ~ 15 nm of size, round in shape and polycrystalline. There is no evidence for silver oxides in the nanostructures. The Si-O-Ag bridges, revealed by infrared spectroscopy, suggest the presence of junction sites between the metallic and the organosilicon parts of the raspberry-like nanoparticles. The silver nanoparticles are found to decorate the organosilicon nanoparticles to form the raspberry-like nanoparticles in the plasma gas-phase, before being deposited. This reveals a very interesting phenomenon of simultaneous growth of the silver- and organosilicon-parts in the plasma without mixing during the nucleation phase.